(3bGfhf GdJLGQI GdHMQjI (B/s - (3Gdabi, YGWa eMeOs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2008)
(3GdSajfI GdfXGe GdbGfhfj ddSajfI , GdMbhb GdYjfjI GdJj JQO Ydi GdSajfI , GdMLR Ydi GdSajfI CTNGU GdedGMI GdHMQjI (B: (3edc GdSajfI , GdCTNGU GdHMQjhf , GdGTNGU GdHQjhf GSJZdGd GdSajfI (B: (3YbO Gdfbd GdHMQj ddHVGFY , YbO Gdfbd GdHMQj ddCTNGU , GjLGQ GdSajfIs
(3HjHdjhZQGajG U(B. 455s
Keywords: (3GSJZdGd GdSajfIs; (3JLGQI HMQjIs; (3bGfhfs; (3fGbd HMQjs